1997
DOI: 10.1177/002194369703400104
|View full text |Cite
|
Sign up to set email alerts
|

A Managerial Perspective: Oral Communi cation Competency Is Most Important for Business Students in the Workplace Jeanne D. Maes

Abstract: Results of two studies show that oral communication is the most important competency for college graduates entering the workforce, and that the oral skills most important for entry level graduates are: following instructions, listening, conversing, and giving feedback. In the first study, 354 managers identified and ranked the competencies and characteristics they consider when hiring college graduates for entry-level positions. Findings reveal that the top three competencies are oral communications, problem-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(32 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…Keyton and colleagues' (2013) findings of verbal workplace communication behaviors mesh with the findings in the current study, particularly with the oral communication skills mentioned with less frequency, to close the gap between instruction and praxis. Previous studies (e.g., Coffelt et al, 2015;Maes et al, 1997) teach. In this way, the gap in awareness between employers and instructors is not as wide as some may believe.…”
Section: Oralmentioning
confidence: 90%
“…Keyton and colleagues' (2013) findings of verbal workplace communication behaviors mesh with the findings in the current study, particularly with the oral communication skills mentioned with less frequency, to close the gap between instruction and praxis. Previous studies (e.g., Coffelt et al, 2015;Maes et al, 1997) teach. In this way, the gap in awareness between employers and instructors is not as wide as some may believe.…”
Section: Oralmentioning
confidence: 90%
“…While there are some exceptions in the literature (Reinsch & Shelby, 1997; Stevens, 2005), most studies conclude that listening is more important in the workplace than is oral expression (Brink & Costigan, 2015; Conrad & Newberry, 2011; Di Salvo & Larsen, 1987; Gray, 2010; Maes et al, 1997; Waner, 1995). In fact, the effects of listening on influencing have been shown to be significant after controlling for the effects of verbal expression (Ames et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Oral communication is defined as “linguistic communication that exchanges information vocally and aurally” (Brink & Costigan, 2015, p. 206). It is among the most important competencies for the workplace (Buckley, Peach, & Weitzel, 1989; Kane, 1993; Maes, Weldy, & Icenogle, 1997; Moody, Stewart, & Bolt-Lee, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown that employers and professional bodies look for novice accounting practitioners with strong communication skills (Bolt-Lee & Foster, 2003;Ulinski & O'callaghan, 2002). There are also studies which contend that oral presentation skills are critical as they allow students to exhibit greater level of cognitive thinking and development (Ulinski & O'callaghan, 2002;Weldy & Icenogle, 1997). Thus, the assessment of oral presentation is crucial for the development of work readiness in graduates (Cabellero & Walker, 2010).…”
Section: Presentations -Including Video Presentationsmentioning
confidence: 99%